Strategi Peningkatan Kinerja Operasional Bagian F&B Product di The Oberoi Beach Resort Bali - Mertasih, Komang Lenni; Rahmawati, Putu Indah; Trianasari (Universitas Pendidikan Ganesha, 2025)
This study aims to identify the condition of kitchen equipment in an effort to improve the operational performance of the F&B Product section at The Oberoi Beach Resort Bali. The method used is a qualitative approach with a semi-structured interview technique with 12 informants who are employees in the kitchen sector. The results of the study indicate that most of the equipment is in good condition but there are still tools that are often damaged and have not been handled systematically. The condition of the equipment has an impact on work efficiency, motivation and employee stress levels. The strategies implemented include equipment maintenance management and improvements in aspects of preventive maintenance and reporting. This study recommends strengthening facility management, improving employee competence and modernizing kitchen equipment as part of a sustainable strategy to improve operational performance.